PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SDN 18 BANDA ACEH - Azkia, Nura; Nena Puspita Sari; Marwah Nazhifah Sitorus; Elly Rizki Diandita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Cooperative Script learning model on improving the learning outcomes of elementary school students. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The subjects of this study consisted of two classes, namely an experimental class and a control class, each comprising 30 students. The experimental class was taught using the Cooperative Script model, while the control class received conventional instruction. Data were collected through learning outcome tests in the form of pretest and posttest, supported by observation of student activities. The data were analyzed using descriptive and inferential statistics, including normality test, homogeneity test, independent sample t-test, and N-Gain analysis to determine the level of improvement in students’ learning outcomes. The results showed that the average posttest score of the experimental class was higher than that of the control class. In addition, the N-Gain value of the experimental class was in the medium to high category, while the control class was in the low to medium category. The hypothesis testing indicated a significant difference between the two classes, suggesting that the use of the Cooperative Script model significantly affects students’ learning outcomes. The implementation of this model encourages active student engagement through reading, summarizing, and explaining the material in pairs, which enhances students’ conceptual understanding. Therefore, the Cooperative Script model can be recommended as an effective alternative learning strategy to improve the quality of learning in elementary schools.